Study on perception and readiness of phase 1 medical students in faculty of medicine and health sciences, UNIMAS on self-directed learning - Low, Zhen Ying; Song, Yeow Leong; Kodiesarn, Y oganantham; Gunasegran, Vilasini (Universiti Malaysia Sarawak (UNIMAS), 2011)
Self-directed learning skill is a must have skill of a future medical doctor as medical field is endless where medical knowledge is unlimited. It is vital to inculcate SDL skills in Phase 1 medical student in order to prepare them for clinical phase which require lot of selfdirected learning. SDL is needed to improve and update their medical knowldge no matter when they are in medical school or even after gruaduating from medical school. This research is carried out to determine duration of study, usages oflearning aids, perceptions towards SDL and readiness of students towards SDL. The study was done among 190 Phase 1 medical students in FMHS,UNIMAS. Data collection was carried out by using questionnaires and analysed using SPSS 17.0 software. It was found out that phase 1 medical students study at average of2-3 hours per day. First year students are having 68 SDL period while second year students have 80 hours of SDL period. In these SDL periods, they only use 2 out of 10 periods ofSDL for study. Study also shows that year 2 students uses learning aids more than first year students but they have poorer perception towards SDL. First year has higher mean of 6.59 than second year students with a mean of 6.38 in perception towards SDL. Higher mean perception is correlate with higher SDLRS score proving that first year student are more ready for Self-Directed Learning method.